A prospective study on vulvovaginal candidiasis: multicentre molecular epidemiology of pathogenic yeasts in China. (23rd December 2021) - Song, N.; Kan, S.; Pang, Q.; Mei, H.; Zheng, H.; Li, D.; Cui, F.; Lv, G.; An, R.; Li, P.; Xiong, Z.; Fan, S.; et al.
Abstract: Background: Vulvovaginal candidiasis (VVC) is frequent in women of reproductive age, but very limited data are available on the epidemiology in cases of VVC in China. Objectives: The current study has been conducted to reveal the prevalence, species distribution of yeast causing VVC and molecular genetics of Candida albicans in China. Methods: Vaginal swabs were collected from 543 VVC outpatients recruited in 12 hospitals in China between September 2017 and March 2018. They were preliminarily incubated on Sabouraud dextrose agar and then positive subjects of which were then transmitted to our institute for further identification. CHROMagar™ was used to isolate Candida species, and all isolates were finally identified by DNA sequencing. Multilocus sequence typing (MLST) was used to analyse phylogenetic relationships of the various C. albicans isolates. Results: Eleven different yeast species were identified in 543 isolates, among which C. albicans (84.7%) was the most frequent, followed by C. glabrata (8.7%). We obtained 117 unique diploid sequence types from 451 clinical C. albicans isolates and 92 isolates (20.4%) belonged to a New Clade. All the strains appearing in the New Clade were from northern China and they were isolated from non‐recurrent VVC. Conclusions: Our findings suggest that C. albicans are still the main cause of VVC in China and the majority of C. albicans isolates belongs to Clade 1 with DST 79 and DST 45 being two most common. Moreover, the New Clade revealed in our study seems to be specific to northern China.